Increasing High School Students' Awareness of Cybercrime Through Digital Literacy at MA Baabussalaam, Jl. K.H. Wahid Hasyim Gang. Sukarmana No. 19 Bojongloa Kaler, Bandung City - Haris Supriatna; Ahmad Maki Asrul Sanit; Galih Septiyadi; Azka Muhammad Sigit; Alya Mulyati Syarifah Wahidah; Devi Sri Damayanti; Sandika Dwi Kurniawan; Yohanes Rionaldo Saputra; Riffa Fisiska Racmat (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2024)
The community service team, comprising academics and students from STMIK Mardira Indonesia, executed an initiative focused on educating about cybercrime as a significant threat to young people engaged in digital technology, particularly secondary school pupils.  The insufficient comprehension of the modalities and perils of cybercrime, including phishing and deepfakes, renders pupils susceptible to victimization.  This Community Service Activity (PKM) seeks to elevate the awareness and understanding of MA BAABUSSALAM students on cybercrime via digital literacy initiatives. An interactive session was conducted for pupils, featuring demonstrations on digital manipulation techniques and online fraud schemes.  The program included a Q&A session and dynamic exchanges to promote a more profound comprehension.  The results indicated an enhancement in students' knowledge of potential risks in the digital realm, together with an increased eagerness to identify and evade dubious digital content or activities.  In conclusion, this activity effectively promoted students' critical awareness and vigilance concerning cyber dangers, underscoring the significance of digital literacy as a protective measure in the digital age.